PASAR TRADISIONAL TOMOHON ( SUATU KAJIAN ANTROPOLOGI ) - Rompas, Geiby Magda Hariet (Universitas Sam Ratulangi, 2013)
Tomohon market is the largest and most comprehensive market which sells a variety of purposes ranging from the Minahasa people cooking spices, ritual paraphernalia, until extreme food. Cultural tourism could not be separated from the role of culture itself. The number tourists visiting a place that is interesting and different from the culture in their place of origin. Curiosity and desire to get satisfaction tourism makes people flocked to tourist activities. Tourism activity generates revenue for the tourism industry, government, local communities and others. The existence of an attraction is also inseparable from the cultural manifestation itself and become tourists to enjoy as a tourist destination. Tomohon government continues to boost market advantages Faithful. Of which serve as centers of Tomohon market commodity vegetables which will then be marketed to the outside Tomohon. City government continues to expose the existence of extreme culinary networking sites via internet or ask for help private companies eg hospitality services or traveling. World tourism company did not escape the attention of Regional Markets as a form of attention in the development of the traditional market town of Tomohon. Famous names Beriman Markets outside the region to make the people who are in other regions and even abroad became curious so as to suck the tourists to visit the place. Thus more and more tourists are coming it will be the more revenue the government. Extreme culinary be the main thing in attracting the attention of tourists seem to produce satisfactory results. Keywords : tourism, culture, market